2021
DOI: 10.1007/978-981-33-6926-9_35
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 and Tuberculosis Classification Based on Chest X-Ray Using Convolutional Neural Network

Abstract: The high rate of patients with tuberculosis (TB) with the graph showing a continual increase requires the research in any sector as the programs to eradicate tuberculosis. One of the applications is the Decision Support System (DSS) that helps the medical experts particularly doctors in diagnosing TB grade 1+. 2+ , and 3+ rapidly. Another problem is related to the imbalance between the number of patients and the number of medical practitioners in the condition of pandemic Corona Virus Disease (Covid-19) today.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 26 publications
(26 reference statements)
1
7
0
Order By: Relevance
“…ML was the most frequently used method to develop CDSS for COVID‐19 diagnosis. The most common ML methods in the reviewed studies were CNN 34–85 . In line with this result, other review studies also indicated CNN to be the most common method to develop a system for COVID‐19 diagnosis 23,25,27,28,30,100 .…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…ML was the most frequently used method to develop CDSS for COVID‐19 diagnosis. The most common ML methods in the reviewed studies were CNN 34–85 . In line with this result, other review studies also indicated CNN to be the most common method to develop a system for COVID‐19 diagnosis 23,25,27,28,30,100 .…”
Section: Discussionsupporting
confidence: 54%
“…These studies also recommended the use of CDSS in future research. Finally, 68 articles met all the inclusion criteria 5,17,34–99 . The flowchart of the selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations